THE IMPORTANCE OF LEARNING ENGLISH AT SCHOOL - Mauliska, Nur; D'Angelo, James F. (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
English language learning in Indonesian schools is a crucial element in preparing students to face globalization and competition in the job market. This study explores the impact of English language learning on cognitive development, educational opportunities, and career prospects. Using a library research method, various literatures from SINTA, WoS and Scopus indexed journals were analyzed to identify the benefits and challenges associated with English language teaching. Findings indicate that English proficiency enhances critical thinking skills, analytical abilities, and provides a competitive edge in the global job market. Despite policies such as the 2013 Curriculum improving English competencies, there are still disparities in teaching quality and resources. Challenges include limited access in rural areas and the need for more interactive pedagogical approaches. This study emphasizes the importance of sustained support from government, schools, and communities, as well as the utilization of educational technology to overcome these barriers. The conclusion of this study is that by improving English proficiency among students, Indonesia can enhance its global competitiveness and better prepare its youth for the era of globalization.